Gaya Hidup Berhubungan dengan Hipertensi - Emdat Suprayitno; Sri Sumarni; Isqi lailatul islami (Wiraraja Medika : Jurnal Kesehatan, 2020)
Abstract Hypertension is a major problem as a risk factor for death in cardiovascular disease caused by genetic and lifestyle factors. The purpose of this study was to analyze the relationship between hypertension and lifestyle in Poja Village, Gapura District. This study used a cross sectional analytic design. The population in this study were 73 people. The sampling technique was simple random sampling and data analysis used the Chi Square test, the data collection technique used online questionnaire forms (google forms). Chi square test results obtained P value = 0.001 <a (0.05), which means that there is a relationship between hypertension and lifestyle in Poja Village, Gapura District. Therefore it is important to always adopt a good and healthy lifestyle to prevent hypertension Keywords: Hypertension, lifestyle, the incidence of hypertension